CD44v6 as innovative sarcoma target for CAR-redirected CIK cells. (4th May 2018) - Leuci, V.; Casucci, G. M.; Grignani, G.; Rotolo, R.; Rossotti, U.; Vigna, E.; Gammaitoni, L.; Mesiano, G.; Fiorino, E.; Donini, C.; Pisacane, A.; ambrosio, L. D.; et al.
ABSTRACT: Purpose of our study was to explore a new immunotherapy for high grade soft tissue sarcomas (STS) based on cytokine-induced killer cells (CIK) redirected with a chimeric antigen receptor (CAR) against the tumor-promoting antigen CD44v6. We aimed at generating bipotential killers, combining the CAR specificity with the intrinsic tumor-killing ability of CIK cells (CAR + .CIK). We set a patient-derived experimental platform. CAR + .CIK were generated by transduction of CIK precursors with a lentiviral vector encoding for anti-CD44v6-CAR. CAR + .CIK were characterized and assessed in vitro against multiple histotypes of patient-derived STS. The anti-sarcoma activity of CAR + .CIK was confirmed in a STS xenograft model. CD44v6 was expressed by 40% (11/27) of patient-derived STS. CAR + .CIK were efficiently expanded from patients (n = 12) and killed multiple histotypes of STS (including autologous targets, n = 4). The killing activity was significantly higher compared with unmodified CIK, especially at low effector/target (E/T) ratios: 98% vs 82% (E/T = 10:1) and 68% vs 26% (1:4), (p<0.0001). Specificity of tumor killing was confirmed by blocking with anti-CD44v6 antibody. CAR + .CIK produced higher amounts of IL6 and IFN-γ compared to control CIK. CAR + .CIK were highly active in mice bearing subcutaneous STS xenografts, with significant delay of tumor growth (p<0.0001) without toxicities. We report first evidence of CAR + .CIK's activity against high grade STS and propose CD44v6 as an innovative target in this setting. CIK are a valuable platform for the translation of CAR-based strategies to challenging field of solid tumors. Our findings support the exploration of CAR + .CIK in clinical trials against high grade STS.